Conceptual design of hydrotechnical installation for sprinkling the tailing dump in the mines and flotation plant Kopaonik - Leposavić - Rajković Branislav; Kamenović Vladan; Ilić Zoran; Obradović Ljubiša; Angelov Goran (Mining and Metallurgy Engineering Bor)
This paper presents a description of operation and main elements of mechanical installation on an example of the conceptual design of the hydrotechnical installation for sprinkling the MFP Kopaonik tailing dump. Calculation for the pump selection is given at the level of conceptual design in the calculation part. Presentation of the PID of installation for sprinkling the tailing dump, as well as the technical characteristics of the main elements of installation, are also given.